Needs and educational interests of literates and illiterates in the age group 10-49 years old - Heidar Toorāni (فصلنامه نوآوری‌های آموزشی, 2016)
The aim of this article was to recognize the educational needs and interests of literates and illiterates in the age group of 10-49 years old in order to find the operational solutions to meet their needs and educational interests. The method of this research was survey and its statistical population included scholars, local reference groups, managers and experts of literacy movement organization, education departments, educators, literates and illiterates in Iran. The research sample included 391 persons who were selected through stratified-random sampling method. The research tools included a researcher-made questionnaire, open and semi-structured interviews and the focus group. The data was analyzed using one sample t-test and the qualitative content analysis method. The results showed that literates and illiterates in the age group 10-49 years old have good inner motivation for learning, therefore when developing the educational content, their interests, attitude, knowledge and skills should be considered.